میرا جی کے تنقیدی تنوعات - Rizwan Faisal; Dr. Hammad Rasool (Khayaban - خیابان, 2021)
Abstruct: Critical services of Meera ji has many angles. He provided the first examples of the applied criticism of modern Urdu poetry. Introduced, commented and translated translations of selected poets of East and West. Laid the foundation of Majlisi criticism in Urdu. He also clarified the poetry of modern Urdu poets in response to the objections of contemporary progressive critics. However, the real significance of his criticism lies in the context in which he appeared. Criticism of Meera ji clarifies its features in the context of modern poetry. Most of the problems and questions of his critique arise from this poetry of modern poetry which he himself kept in mind.